Integrative Guidelines for the Nursing Care of Patients Using Cannabis for Medicinal Purposes - Maneewat, Khomapak; Nimmaanrat, Sasikaan; Puttawibul, Puttisak; Kantabanlang, Yupawadee; Siripituphum, Duangsuda; Sawasdinaruenart, Sumamita; Bilalee, Sahas; Wangkulangkul, Piyanun (Princess of Naradhiwas University Journal, 2023)
In 2019, Thai federal government has announced the legal use of cannabis in medical care. Since then, the number of cannabis users has been rising up due to its popularity. Resulting in a higher chance of nurses and other healthcare providers in dealing with this group of patients. Presently, medical cannabis knowledge is relatively new and not yet integrated in nursing curriculum and its training course is barely widespread. Moreover, there is no ideal nursing practice guideline announced in Thailand that could develop in other contexts. Hence, it may affect the performance of nurses towards the patients. Culturally sensitive holistic-integrative nursing guidelines for the nursing care of patients using cannabis for medical purposes was therefore developed based on the current best available evidence using the ADAPTE process for guideline adaptation proposed by the ADAPTE collaboration and the drafting guideline was also approved by expert panels and revised as suggested. This final draft guideline consisted of 4 main categories with 22 sub-sections, including; essential knowledge of medical cannabis in section 1 which was contained with 8 sub-recommendations. Section 2 was provided with the best care for medical cannabis users which was obtained with 6 sub-suggestions. Section 3 was about administration of medicines or medicinal cannabis products which was consisted of 4 sub-advices. Finally, section 4, concerned about ethics in the administration of medicines or medicinal cannabis products which was consisted of 4 sub-suggestions. The developed guidelines would lead to the planning process for trials with the target population in implementation of guidance, results evaluation, effectiveness, flexibility, easiness, feasibility in usage, contributing factors, and obstacles in practicing for further promulgation.